Are female daycare workers at greater risk of cytomegalovirus infection? A secondary data analysis of CMV seroprevalence between 2010 and 2013 in Hamburg, Germany - Stranzinger, Johanna; Kozak, Agnessa; Schilgen, Benjamin; Paris, Diana; Nießen, Thomas; Schmidt, Lutz; Wille, Andreas; Wagner, Norbert L.; Nienhaus, Albert (German Medical Science GMS Publishing House, 2016)
Background: Close contact with asymptomatic children younger than three years is a risk factor for a primary cytomegalovirus (CMV) infection. In pregnant women, such primary infection increases the risk of CMV-induced feto- or embryopathy. Daycare providers have therefore implemented working restrictions for pregnant daycare workers (DCWs) in accordance with legislation and guidelines for maternity protection. However, little is known about the infection risk for DCWs. We therefore compared the prevalence of CMV antibodies of pregnant DCWs to that of female blood donors (BDs).Method: In a secondary data analysis, the prevalence of anti-CMV IgG among pregnant DCWs (N=509) in daycare centers (DCCs) was compared to the prevalence of female first-time BDs (N=14,358) from the greater region of Hamburg, Germany. Data collection took place between 2010 and 2013. The influence of other risk factors such as age, pregnancies and place of residence was evaluated using logistic regression models. Results: The prevalence of CMV antibodies in pregnant DCWs was higher than in female BDs (54.6 vs 41.5%; OR 1.6; 95%CI 1.3-1.9). The subgroup of BDs who had given birth to at least one child and who lived in the city of Hamburg (N=2,591) had a prevalence of CMV antibodies similar to the prevalence in pregnant DCWs (53.9 vs 54.6%; OR 0.9; 95%CI 0.8-1.2). Age, pregnancy history and living in the center of Hamburg were risk factors for CMV infections.Conclusion: The comparison of pregnant DCWs to the best-matching subgroup of female first-time BDs with past pregnancies and living in the city of Hamburg does not indicate an elevated risk of CMV infection among DCWs. However, as two secondary data sets from convenience samples were used, a more detailed investigation of the risk factors other than place of residence, age and maternity was not possible. Therefore, the CMV infection risk in DCWs should be further studied by taking into consideration the potential preventive effect of hygiene measures.